Composite negative electrode material and preparation method thereof, and lithium ion battery

By adopting the skeleton structure and cladding layer of composite negative electrode material, the problem of large volume expansion of lithium-ion battery negative electrode material during lithium alloying is solved, and higher cycle stability and electrochemical performance are achieved.

CN114725327BActive Publication Date: 2025-03-25BTR NEW MATERIAL GRP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110013364.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-01-06
Publication Date
2025-03-25
Estimated Expiration
2041-01-06

AI Technical Summary

Technical Problem

The volume expansion of existing lithium-ion battery anode materials during lithium alloying process, resulting in material powdering, deterioration of electrochemical performance and decreased cycle stability, making it difficult to commercially apply.

Method used

A composite negative electrode material is used, which includes a skeleton structure with a primary particle core and a surface coating. The skeleton of the primary particle consists of the main skeleton and branches, which extend to the surface of the particle, forming a three-dimensional network structure that enhances electron conduction and ion diffusion. At the same time, the cladding layer on the surface of the core material further improves structural stability and cyclic stability.

Benefits of technology

It effectively reduces the volume expansion of the material, improves cycle stability and electrochemical properties, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114725327B_ABST
    Figure CN114725327B_ABST
Patent Text Reader

Abstract

The present application relates to the field of negative electrode materials, and provides a composite negative electrode material and a preparation method thereof, and a lithium-ion battery, wherein the composite negative electrode material includes a core and a coating formed on the surface of the core; the core is a primary particle, and the primary particle includes a skeleton, and the skeleton includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle; the primary particle is a macroporous structure, and a pore is formed inside the primary particle, and the pore extends to the surface of the primary particle; the coating includes a carbon layer, a metal oxide layer, and a metal nitride layer. The composite negative electrode material and the preparation method thereof of the present application are low-cost, can be mass-produced, can reduce the volume expansion of the negative electrode material, and improve the structural stability and cycle stability of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of negative electrode materials, and in particular to a composite negative electrode material and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their advantages such as high energy density, high output power, long cycle life and low environmental pollution. In order to improve the energy density of batteries, the research and development of high-capacity negative electrode materials such as Si, Ge, Sn, Sb and B are becoming more and more mature. However, these negative electrode materials have a large volume expansion during the alloying process with lithium, and will be pulverized and fall off the current collector during the charging and discharging process, causing the active material to lose electrical contact with the current collector, resulting in poor electrochemical performance, capacity attenuation, and decreased cycle stability, making it difficult to obtain commercial applications. Summary of the invention

[0003] In view of this, the present application proposes a composite negative electrode material and a preparation method thereof, and a lithium-ion battery that can reduce expansion and improve cycle stability.

[0004] A composite negative electrode material, comprising a core and a coating layer formed on the surface of the core; wherein:

[0005] The inner core is a primary particle. The primary particle includes a skeleton. The skeleton includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle.

[0006] The negative electrode material of this embodiment is a primary particle. The main skeleton inside the primary particle and the multiple branches extending from the main skeleton to the surface of the primary particle are a whole. The entire skeleton structure enhances the electronic conduction and ion diffusion of the material, which can effectively release the stress after lithiation and avoid stress concentration at the grain boundary causing material breakage and pulverization.

[0007] Compared with the secondary porous structure formed by the accumulation of nanoparticles, the negative electrode material has the advantage of a more stable integrated structure, and can have both a smaller specific surface area and a higher porosity. The present invention is a complete particle, the entire skeleton is connected, the electron conduction and ion diffusion of the enhanced material can effectively release the stress after lithiation, and avoid stress concentration leading to material pulverization. The porous material assembled by the secondary particles has obvious grain boundaries between the particles, which leads to lithiation stress concentration, particle breakage, and destruction of the entire structure, which ultimately leads to deterioration of electrochemical performance.

[0008] In addition, the coating layer on the surface of the core material can further improve the structural stability and cycle stability of the negative electrode material, while further alleviating the volume expansion of the negative electrode material.

[0009] In one embodiment, the main skeleton is a three-dimensional network structure;

[0010] In one embodiment, each of the branches is a separate grain;

[0011] In one embodiment, the size of the grains is 30nm-100nm;

[0012] In one embodiment, the maximum width of the cross section of the branch is 20nm-250nm, and the maximum length of the cross section of the branch is 100nm-1500nm;

[0013] In one embodiment, the branches are selected from at least one of rod-shaped nanoparticles, nanosheets, nanowires and nanotubes.

[0014] A composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein the core is a primary particle, the primary particle is a macroporous structure, a pore is formed inside the primary particle, and the pore extends to the surface of the primary particle.

[0015] The pore structure of the negative electrode material extending to the surface of the primary particles has the following advantages: 1. It can reduce the expansion of the lithium battery while improving the lithium storage performance. It can not only alleviate the volume expansion during the lithium insertion process, but also provide space for internal expansion for lithiation, so that the electrode material expands inward after lithiation and reduces the thickness of the entire electrode film, greatly improving the safety of lithium-ion batteries. 2. It provides a channel for the flow of electrolyte, which is conducive to the contact of the electrolyte. The pore structure can also bring higher tap density, which can increase the volume energy density of the battery.

[0016] In one embodiment, the diameter of the pore is 10 nm-150 nm; the depth of the pore is 50 nm-1500 nm.

[0017] A composite negative electrode material comprises a core and a coating formed on the surface of the core; wherein the core is a primary particle, a through hole is formed inside the primary particle, and the porosity of the primary particle is not less than 30%.

[0018] The primary particles of the present application have a high porosity, which can effectively alleviate the volume expansion of the negative electrode material by more than 300%. Combined with the advantages of the through-hole structure, the pore structure after lithiation can also remain intact. The porosity of the prior art is relatively low and cannot meet the huge volume expansion of the negative electrode material (such as silicon). After the pores are filled after lithiation, the pores are eventually blocked due to electrochemical sintering, and the porous structure cannot be maintained.

[0019] In one embodiment, the coating layer includes at least one of a carbon layer, a metal oxide layer and a metal nitride layer;

[0020] The coating layer includes a carbon layer, and the mass percentage content of the carbon is 2% to 50% based on the mass percentage content of the composite negative electrode material being 100%;

[0021] In one embodiment, the coating layer includes at least one of a graphene layer and an amorphous carbon layer;

[0022] In one embodiment, the coating layer includes a graphene layer, and the graphene layer has a wrinkled structure;

[0023] In one embodiment, the maximum peak-to-valley height difference of the roughness of the corrugated structure is greater than 10 nm and less than 1 μm, and the distance between two adjacent wave peaks or two adjacent wave valleys of the corrugated structure is greater than 10 nm and less than 1 μm;

[0024] In one embodiment, according to the classification of the curvature of the fold surface of the fold structure, the fold structure is selected from at least one of arc folds, sharp-edged folds, and fan-shaped folds;

[0025] In one embodiment, the fold structure is classified according to the axial occurrence and the two-wing occurrence of the fold structure, and the fold structure is selected from at least one of upright folds, oblique folds, inverted folds and horizontal folds;

[0026] In one embodiment, the coating layer includes an amorphous carbon layer, and the thickness of the amorphous carbon layer is 5nm to 150nm;

[0027] In one embodiment, the coating layer includes a metal oxide layer, and the mass percentage content of the metal oxide is 2% to 60% based on the mass percentage content of the composite negative electrode material as 100%;

[0028] In one embodiment, the coating layer includes a metal oxide layer, and the metal element in the metal oxide layer includes at least one of Ti, V, Nb, Ta, W and Zr;

[0029] In one embodiment, the molar ratio of the metal element to the oxygen element in the metal oxide layer is 1:(0.1-3); the thickness of the metal oxide layer is 1nm-200nm;

[0030] In one embodiment, the coating layer includes a metal nitride layer, and based on the mass percentage of the composite negative electrode material being 100%, the mass percentage content of the metal nitride is 2% to 70%.

[0031] In one embodiment, the coating layer includes a metal nitride layer, and the metal element in the metal nitride layer includes at least one of Ti, V, Nb, Ta, W and Zr.

[0032] In one embodiment, the metal nitride layer has a thickness of 1 nm to 250 nm.

[0033] In one embodiment, the primary particles are selected from at least one of silicon, germanium, antimony, tin, and boron;

[0034] In one embodiment, the median particle size of the primary particles is 0.2 μm to 15 μm;

[0035] In one embodiment, the specific surface area of ​​the primary particles is 5 m 2 / g~100m 2 / g;

[0036] In one embodiment, the porosity of the primary particles is 30% to 70%;

[0037] In one embodiment, the tap density of the primary particles is 0.2 g / cm 3 ~0.8g / cm 3 ;

[0038] In one embodiment, the powder compaction density of the primary particles is 1.2 g / cm 3 ~1.8g / cm 3 ;

[0039] In one embodiment, the median particle size of the composite negative electrode material is 0.1 μm to 15 μm;

[0040] In one embodiment, the specific surface area of ​​the composite negative electrode material is 1 m 2 / g~150m 2 / g;

[0041] In one embodiment, the porosity of the composite negative electrode material is 30% to 70%.

[0042] A method for preparing a composite negative electrode material comprises the following steps:

[0043] Placing a mixture containing an NM alloy and a halogen-containing six-membered ring organic compound in a protective atmosphere for a replacement reaction to obtain a reaction product, wherein the reaction product includes an oxide of M and a halide of M;

[0044] removing the oxide of M and the halide of M to obtain a composite negative electrode material;

[0045] The N in the NM alloy includes at least one of silicon, germanium, antimony, tin and boron;

[0046] The M in the NM alloy includes at least one of magnesium, aluminum, calcium and zinc.

[0047] The preparation method prepares the negative electrode material through a one-step composite method. The NM alloy directly reacts with the six-membered ring organic matter at high temperature to remove the metal M component in the NM alloy, and at the same time, a carbon layer is deposited in situ on the surface of the N material. The overall reaction is mild and has no by-products. The N material structure is complete and stable, and the carbon layer is deposited evenly. The raw materials involved in the reaction are all commonly used alloys, organic matter and metal salts, which can reduce costs.

[0048] In one embodiment, the molar ratio of the NM alloy to the halogen-containing six-membered ring organic compound is 1:(0.2-6);

[0049] In one embodiment, the halogen-containing six-membered ring organic compound includes at least one of halogenated cyclohexanes and their derivatives, halogenated benzenes, halogenated benzoic acids and halogenated anilines, and the halogen includes at least one of fluorine, chlorine and bromine;

[0050] In one embodiment, when the halogen-containing six-membered ring organic compound uses cyclohexane halide, the mixture further includes a cleavage inhibitor, wherein the cleavage inhibitor includes an amide compound and a cyanate;

[0051] In one embodiment, the molar ratio of the silicon alloy to the amide compound is 1:(0.1-10); the molar ratio of the silicon alloy to the cyanate is 1:(0.1-10);

[0052] In one embodiment, the amide compound includes at least one of carbonamide, formamide, acetamide, dimethylformamide and lactam;

[0053] The cyanate comprises at least one of potassium cyanate, sodium cyanate and ammonium cyanate;

[0054] In one embodiment, the reaction temperature of the replacement reaction is 200°C to 1000°C, and the reaction time is 1h to 24h;

[0055] In one embodiment, the protective atmosphere comprises at least one of helium, neon, argon, krypton and xenon;

[0056] In one embodiment, the method for removing the oxide of M and the halide of M comprises pickling, and the mass concentration of the acid solution used in the pickling is 1 mol / L to 5 mol / L;

[0057] In one embodiment, the acid solution used for pickling includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

[0058] A method for preparing a composite negative electrode material comprises the following steps:

[0059] The composite is subjected to a replacement reaction under a vacuum environment to obtain a reaction product, wherein the reaction product includes an oxide of M1, and the composite includes an N1-M1 material with a metal oxide layer formed on the surface;

[0060] Removing the oxide of M1 to obtain a composite negative electrode material;

[0061] The N1 in the N1-M1 material includes at least one of silicon, germanium, antimony, tin and boron;

[0062] The M1 in the N1-M1 material includes at least one of magnesium, aluminum, calcium and zinc.

[0063] In this embodiment, a metal oxide layer is coated on the surface of the N1-M1 material, and the N1-M1 material undergoes a replacement reaction with part of the metal oxide layer at high temperature, thereby removing the M1 component in the N1-M1 material and generating an incompletely reacted metal oxide layer on the surface of the N1 material. After pickling, a composite negative electrode material can be obtained. In this solution, the metal oxide layer has the advantages of good rigidity and excellent density, and the current and flexible carbon layer material can effectively inhibit the volume expansion of N1 and cause the destruction of the entire structure, reduce the volume expansion of the material, and avoid contact between the electrolyte and the silicon negative electrode, reduce side reactions, and improve the primary effect of the entire composite material.

[0064] A method for preparing a composite negative electrode material comprises the following steps:

[0065] The composite is subjected to heat treatment under a protective atmosphere and then subjected to nitridation treatment to obtain a reaction product, wherein the reaction product includes an oxide of M1, and the composite includes an N1-M1 material with a metal oxide layer formed on the surface;

[0066] Removing the oxide of M1 to obtain a composite negative electrode material;

[0067] The N1 in the N1-M1 material includes at least one of silicon, germanium, antimony, tin and boron;

[0068] The M1 in the N1-M1 material includes at least one of magnesium, aluminum, calcium and zinc.

[0069] After coating the surface of the N1-M1 material with a layer of metal oxide layer, heat treatment is performed under a protective atmosphere to ensure, on the one hand, that the N1-M1 material undergoes a replacement reaction with part of the metal oxide layer to remove the metal M1 component in the N1-M1 material; on the other hand, the oxide is ensured to be transformed from amorphous to crystalline at high temperature and normal pressure. Further nitridation treatment is performed to nitride the metal oxide layer on the surface of the inner core into metal nitride. In this solution, the metal nitride layer not only has good rigidity, but also has excellent conductivity, which can effectively alleviate the volume expansion of silicon while increasing the conductivity of the material, improving the rate capability of the material, reducing the irreversible capacity loss of the material, and bringing high capacity.

[0070] In one embodiment, the N1-M1 material is at least one of an intermetallic compound and an alloy;

[0071] In one embodiment, the forming of the metal oxide layer on the surface of the N1-M1 material comprises at least one of a hydrothermal method, a sol-gel method, a precipitation method, a chemical vapor deposition method, a magnetron sputtering method, and a solid phase reaction method;

[0072] In one embodiment, the metal element in the metal oxide layer includes at least one of Ti, V, Nb, Ta, W and Zr;

[0073] In one embodiment, the vacuum degree in the vacuum environment is less than 1000 Pa;

[0074] In one embodiment, the reduction reaction temperature is 500°C-1100°C, and the holding time is 1h-48h;

[0075] In one embodiment, the heat treatment temperature is 500° C.-800° C., and the holding time is 1 h to 24 h; the protective atmosphere includes at least one of helium, neon, argon, krypton and xenon;

[0076] In one embodiment, the nitriding treatment is carried out at 400°C-950°C for 2h-24h; the atmosphere of the nitriding treatment is at least one of an ammonia atmosphere and a nitrogen atmosphere;

[0077] In one embodiment, the method for removing the oxide of M is acid washing.

[0078] A lithium ion battery comprises the composite negative electrode material or the negative electrode material prepared by the method for preparing the composite negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1 A schematic diagram of the structure of the composite negative electrode material provided in this embodiment;

[0080] Figure 2 A schematic diagram of the graphene layer structure of the composite negative electrode material provided in this embodiment;

[0081] Figure 3 A schematic diagram of a process for preparing a composite negative electrode material provided in this embodiment;

[0082] Figure 4 A schematic diagram of the synthesis process of the silicon-carbon composite negative electrode material provided in this embodiment;

[0083] Figure 5 A schematic diagram of the synthesis process of the silicon / metal oxide and silicon / metal nitride composite negative electrode materials provided in this embodiment;

[0084] Figure 6a This is a scanning electron microscope image of the silicon-carbon composite negative electrode material provided in Example 1;

[0085] Figure 6b Another scanning electron microscope image of the silicon-carbon composite negative electrode material provided in Example 1;

[0086] Figure 7 XRD diagram of the silicon-carbon composite negative electrode material provided in Example 1;

[0087] Figure 8 This is the Raman image of the silicon-carbon composite negative electrode material provided in Example 1;

[0088] Fig. 9 The cycle performance curve of the silicon-carbon composite negative electrode material provided in Example 1. DETAILED DESCRIPTION

[0089] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0090] At present, in lithium-ion batteries, negative electrode materials are one of the key materials that affect their charge and discharge performance. The existing negative electrode materials are graphite-based carbon materials, and the theoretical lithium storage capacity of carbon materials is only 372mA h / g, which cannot meet people's demand for high energy density materials. Negative electrode materials such as Si, Ge, Sn, Sb and B can bring high energy density due to their high mass capacity and low voltage platform. However, these negative electrode materials will produce huge volume expansion during the alloying process with lithium, resulting in pulverization of the negative electrode material, loss of electrical contact, and rapid capacity decay. For example, silicon has a very high theoretical capacity (about 4200mA h / g) as a negative electrode material for lithium-ion batteries, but the volume expansion of silicon negative electrode materials during lithium extraction is large (>300%), and it is easy to pulverize and fall from the current collector during the charge and discharge process, so that the active material loses electrical contact with the current collector, resulting in poor electrochemical performance. Therefore, the large volume change effect easily leads to poor cycle stability and is difficult to commercialize. In order to improve the cycle stability of lithium-ion batteries, the embodiment of the present application provides a composite negative electrode material with low expansion and good stability.

[0091] Specifically, Figure 1 As shown, the composite negative electrode material includes a core 10 and a coating layer 20 formed on the surface of the core 10; wherein,

[0092] The inner core 10 is a primary particle. The primary particle includes a skeleton. The skeleton includes a main skeleton 11 located inside the primary particle and a plurality of branches 12 extending from the main skeleton 11 to the surface of the primary particle.

[0093] Please read further Figure 1 The core 10 of this embodiment is a primary particle, the primary particle is a macroporous structure, and a pore 13 is formed inside the primary particle, and the pore 13 extends to the surface of the primary particle. According to the definition of the International Association of Pure and Applied Chemistry (IUPAC), a pore with a diameter greater than 50 nm is called a macropore.

[0094] The negative electrode material of this embodiment is a primary particle. The main skeleton inside the primary particle and the multiple branches extending from the main skeleton to the surface of the primary particle are a whole. The entire skeleton structure enhances the electronic conduction and ion diffusion of the material, which can effectively release the stress after lithiation and avoid stress concentration at the grain boundary causing material breakage and pulverization.

[0095] The pore structure of the negative electrode material extending to the surface of the primary particles has the following advantages: 1. It can reduce the expansion of the lithium battery while improving the lithium storage performance. It can not only alleviate the volume expansion during the lithium insertion process, but also provide space for internal expansion for lithiation, so that the electrode material expands inward after lithiation and reduces the thickness of the entire electrode film, greatly improving the safety of lithium-ion batteries. 2. It provides a channel for the flow of electrolyte, which is conducive to the contact of the electrolyte. The pore structure can also bring higher tap density, which can increase the volume energy density of the battery.

[0096] Compared with the secondary porous structure formed by the accumulation of nanoparticles, the negative electrode material prepared by this embodiment has the advantage of a more stable integrated structure, and can have both a smaller specific surface area and a higher porosity. The present invention is a complete particle, the entire skeleton is connected, the electron conduction and ion diffusion of the enhanced material can effectively release the stress after lithiation, and avoid stress concentration leading to material pulverization. The porous material assembled by the secondary particles has obvious grain boundaries between the particles, which leads to lithiation stress concentration, particle breakage, and destruction of the entire structure, which ultimately leads to deterioration of electrochemical performance.

[0097] In addition, the coating layer on the surface of the core material can further improve the structural stability and cycle stability of the negative electrode material, while further alleviating the volume expansion of the negative electrode material.

[0098] In some embodiments, the main skeleton is a three-dimensional network structure;

[0099] In some embodiments, a single branch is a separate grain; there is no obvious grain boundary between the branch and the main skeleton, and the grains are dispersed on the surface of the primary particle. In the prior art solution, the branches on the porous silicon secondary particles are mainly composed of multiple small grains with more grain boundaries. Compared with this structure, the branches on the primary particles in this embodiment are a single large grain without too many grain boundaries. After lithiation, the stress can be better dispersed to avoid stress concentration and material damage; at the same time, the crystal plane curves of a single grain are the same, which is more conducive to reducing the relative volume expansion of the material in a certain direction, while the volume expansion of the structure composed of multiple small grains is relatively large, and the structural stability is also relatively poor, resulting in poor cycle stability.

[0100] Specifically, the size of the grains is 30 nm-100 nm; illustratively, the size of the grains may be 30 nm, 45 nm, 50 nm, 60 nm, 75 nm, or 100 nm.

[0101] Please continue reading Figure 1 The maximum width 12W of the cross section of the branch 12 is 20 nm to 250 nm, and the maximum length 12L of the cross section of the branch 12 is 100 nm to 1500 nm.

[0102] Exemplarily, the maximum width 12W of the cross section of branch 12 can be, for example, 20nm, 40nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm or 250nm, and the maximum length 12L of the cross section of branch 12 can be, for example, 100nm, 200nm, 300nm, 400nm, 500nm, 800nm, 1000nm, 1200nm or 1500nm, without limitation herein.

[0103] In some embodiments, the branches are selected from at least one of rod-shaped nanoparticles, nanosheets, nanowires, and nanotubes.

[0104] In some embodiments, the diameter of the pore 13 measured by the mercury injection test method is 10nm-150nm; the depth of the pore is 50nm-1500nm. Exemplarily, the pore diameter can be 10nm, 50nm, 60nm, 80nm, 100nm or 150nm, which is not limited here. The depth of the pore 13 can be 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 800nm ​​or 1000nm, which is not limited here. The depth of the pore can be changed by controlling the reaction time and reaction temperature (generally, the longer the reaction time and the higher the reaction temperature, the deeper the depth of the pore.)

[0105] In some embodiments, the primary particles are selected from at least one of silicon, germanium, tin, boron and antimony; the skeleton thereof may be a silicon skeleton, a germanium skeleton, a tin skeleton, a boron skeleton, an antimony skeleton, etc. If the primary particles are selected from silicon materials, the primary particles include a silicon skeleton, including a main skeleton located inside the primary particles and a plurality of branches extending from the main skeleton to the surface of the primary particles. The skeleton structures of germanium, boron, tin and antimony are similar to the above-mentioned silicon skeleton structure.

[0106] In some embodiments, the median particle size of the primary particles is 0.2 μm to 15 μm, such as 0.2 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm or 15 μm, etc. Preferably, it is 0.5 μm to 10 μm, and more preferably, it is 1 μm to 5 μm.

[0107] In some embodiments, the specific surface area of ​​the primary particles is 5 m 2 / g~00m 2 / g, for example 5m 2 / g, 10m 2 / g, 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 80m 2 / g or 100m 2 / g, etc. Preferably 10m 2 / g~50m 2 / g.

[0108] In some embodiments, the tap density of the primary particles is 0.2 g / cm 3 ~0.8g / cm 3 , for example 0.2g / cm 3 , 0.3g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 or 0.8g / cm 3 etc. Preferably 0.4 g / cm 3 ~0.7g / cm 3 .

[0109] In some embodiments, the powder compaction density of the primary particles is 1.2 g / cm 3 ~1.8g / cm 3 , for example 1.2 g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3, 1.6g / cm 3 or 1.8 g / cm 3 etc., preferably 1.4 g / cm 3 ~1.7g / cm 3 ;

[0110] In some embodiments, the median particle size of the composite negative electrode material is 0.1 μm to 15 μm. Optionally, the median particle size of the composite negative electrode material can be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., which are not limited here. The median particle size of the composite negative electrode material is preferably 0.5 μm to 10 μm, more preferably 1 μm to 8 μm.

[0111] The specific surface area ratio of the composite negative electrode material is 1m 2 / g~150m 2 / g. Optionally, the specific surface area ratio of the composite negative electrode material can be 1m 2 / g, 5m 2 / g, 10m 2 / g, 20m 2 / g, 30m 2 / g, 40m 2 / g, 50m 2 / g, 60m 2 / g, 70m 2 / g、100m 2 / g, 120m 2 / g or 150m 2 / g, etc., which are not limited here; the specific surface area ratio of the composite negative electrode material is preferably 1m 2 / g~50m 2 / g. Understandably, the smaller the specific surface area, the better. Too large a specific surface area will easily lead to the formation of SEI film, consume too much irreversible lithium salt, and reduce the initial efficiency of the battery. Considering the cost of the preparation process, the specific surface area is controlled within 10m 2 / g~50m 2 / g.

[0112] In some embodiments, the coating layer includes at least one of a carbon layer, a metal oxide layer, and a metal nitride layer; the carbon layer, the metal oxide layer, and the nitride layer can further improve the conductivity, structural stability, and cycle stability of the negative electrode material, while further alleviating the volume expansion of the negative electrode material;

[0113] Wherein, the coating layer includes a carbon layer, and further, the carbon layer includes at least one of a graphene layer and an amorphous carbon layer;

[0114] Furthermore, the graphene layer has a wrinkled structure, and the wrinkled morphology of the graphene layer can provide more active sites, thereby further improving the conductivity and rate performance of the negative electrode material;

[0115] like Figure 2 As shown, the wrinkle structure includes a protrusion (peak) 201 and a depression (valley) 202, a depression 202 is between two adjacent protrusions 201, and a protrusion 201 is between two adjacent depressions 202; wherein, the surface roughness Rz (maximum peak-to-valley height) of the wrinkle structure is greater than 10nm and less than 1μm, further, Rz may be greater than 50nm and less than 500nm, further, Rz may be greater than 100nm and less than 350nm. The distance H between the highest points of two adjacent protrusions or the lowest points of two depressions is greater than 10nm and less than 1μm; further, H is greater than 50nm and less than 800μm, further, H is greater than 100nm and less than 500nm.

[0116] Specifically, the pleat structure is classified according to the curvature of the pleat surface, and the pleat structure can be selected from at least one of arc pleats, sharp-edged pleats and fan-shaped pleats; further, the pleat structure can have arc pleats, sharp-edged pleats and fan-shaped pleats at the same time.

[0117] The fold structure is classified according to the axial orientation and the two-wing orientation. The fold structure can be selected from at least one of upright folds, oblique folds, inverted folds and recumbent folds; further, the fold structure can have upright folds, oblique folds, inverted folds and recumbent folds at the same time.

[0118] The graphene layer has the above-mentioned wrinkled structure, which can provide more active sites, thereby further improving the conductivity and rate performance of the negative electrode material.

[0119] In some embodiments, the carbon layer includes an amorphous carbon layer, and the thickness of the amorphous carbon layer is 5 nm to 150 nm;

[0120] In some embodiments, based on the mass percentage of the composite negative electrode material being 100%, the mass percentage of carbon is 2% to 50%;

[0121] In some embodiments, the coating layer includes a metal oxide layer, and the metal in the metal oxide layer includes at least one of Ti, V, Nb, Ta, W and Zr;

[0122] The molar ratio of the metal element to the oxygen element in the metal oxide layer is 1:(0.1-3); the thickness of the metal oxide layer is 1nm-200nm;

[0123] Taking the mass percentage of the composite negative electrode material as 100%, the mass percentage of the metal oxide is 2% to 60%;

[0124] In some embodiments, the coating layer includes a metal nitride layer, the metal element in the metal nitride layer includes at least one of Ti, V, Nb, Ta, W and Zr, and further, the thickness of the metal nitride layer is 1 nm to 250 nm.

[0125] Taking the mass percentage of the composite negative electrode material as 100%, the mass percentage of the metal nitride is 2% to 70%.

[0126] The metal oxide layer and its nitride layer act as a rigid protective shell to prevent the volume expansion of the primary particles from bursting the entire material, ensuring excellent structural stability and long cycle life.

[0127] On the other hand, the composite negative electrode material includes a core 10 and a coating 20 formed on the surface of the core 10; the core 10 is a primary particle, a through hole is formed inside the primary particle, and the porosity of the primary particle is not less than 30%. The primary particles of the present invention have a high porosity, which can effectively alleviate the volume expansion of the negative electrode material by more than 300%. Combined with the advantages of the macroporous through-structure, the pore structure after lithiation can also remain intact. The prior art has a low porosity and a large number of micropores and mesopores, which cannot meet the huge volume expansion of the negative electrode material (such as silicon). After the pores are filled after lithiation, the pores are eventually blocked due to electrochemical sintering, and the porous structure cannot be maintained.

[0128] Furthermore, the porosity of the primary particles is 30% to 70%, for example, 30%, 35%, 40%, 50%, 55%, 60% or 70%, etc., preferably 40% to 60%.

[0129] The primary particles and coating layer of this embodiment are as described above and will not be described again here.

[0130] When the coating layer is a carbon layer, a method for preparing a composite negative electrode material in one embodiment is as follows: Figure 4 As shown, the method includes the following steps S100 to S400:

[0131] S100, preparing NM alloy;

[0132] In some embodiments, N in the NM alloy includes at least one of Si, Ge, Sn, B and Sb; M in the NM alloy includes at least one of Mg, Al, Zn and Ca. In a specific example, the NM alloy can be Si-Mg alloy, Si-Al alloy, Ge-Mg alloy, Ge-Al alloy, etc. Different types of alloys can obtain branches of different shapes, including at least one of rod-shaped nanoparticles, nanosheets, nanowires and nanotubes.

[0133] In some embodiments, the NM alloy preparation method is to mix N powder and active metal M and then heat them under a protective gas to react to obtain the NM alloy.

[0134] The particle size of the N powder is 0.1 μm to 15 μm, and specifically can be 0.1 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm or 15 μm, etc., which is not limited here.

[0135] The powder particle size of the active metal M is 0.1 μm to 80 μm, and specifically can be 0.1 μm, 5 μm, 10 μm, 20 μm, 40 μm, 50 μm or 80 μm, etc., which is not limited here.

[0136] The molar ratio of N powder to active metal M is 1:(1-3), and can be specifically 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, which is not limited here.

[0137] The temperature of the heating reaction is 400°C to 900°C, for example, 400°C, 500°C, 600°C, 700°C, 800°C or 900°C.

[0138] The heat preservation time of the heating reaction is 2 hours to 8 hours, for example, it can be 2 hours, 4 hours, 6 hours or 8 hours, which is not limited here.

[0139] The heating rate of the heating reaction is 1°C / min to 10°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 8°C / min or 10°C / min, which is not limited here.

[0140] In the present application, by controlling parameters such as silicon powder particle size, active metal particle size, reaction temperature, reaction time, etc., it is beneficial to the formation of NM alloy and improves the doping uniformity of metal elements in NM alloy.

[0141] Of course, the NM alloy can also be prepared by other preparation methods, such as high-energy ball milling, vacuum smelting, hot pressing sintering, etc. It is understandable that the NM alloy can be obtained commercially, and step S100 can be omitted in this case.

[0142] In some embodiments, the mass percentage content of N in the NM alloy is 15% to 60%. Optionally, the mass percentage content of N can be 15%, 20%, 30%, 40%, 50% or 60%, which is not limited here. In a specific embodiment, the NM alloy can be, for example, at least one of a silicon-magnesium alloy, a silicon-aluminum alloy, a silicon-calcium alloy, and a silicon-zinc alloy. It can be understood that the size and porosity of the pores of the N material can be changed by controlling the composition of the NM alloy. Generally, the higher the N content in the NM alloy, the smaller the pore size. The depth of the pore can be changed by controlling the heating reaction time and the reaction temperature. Generally, the longer the reaction time and the higher the reaction temperature, the deeper the depth of the pore.

[0143] In a specific embodiment, the method further comprises:

[0144] The obtained NM alloy is pulverized to adjust the particle size of the NM alloy powder to 0.1 μm to 15 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm or 15 μm, which is not limited here.

[0145] Specifically, the pulverizing equipment includes at least one of a planetary ball mill, a sand mill and an air flow pulverizer. It can be understood that the smaller the particle size of the NM alloy, the larger its specific surface area, and the more fully it can react during the dealloying heat treatment.

[0146] S200, mixing the NM alloy and the halogen-containing six-membered ring organic matter to obtain a mixture.

[0147] Specifically, the molar ratio of the NM alloy to the halogen-containing six-membered ring organic matter is 1:(0.2-6), for example, it can be 1:0.2, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5 or 1:6, which is not limited here.

[0148] Specifically, the halogen-containing six-membered ring organic compound includes at least one of halogenated cyclohexane and its derivatives, halogenated benzene, halogenated benzoic acid and halogenated aniline. The halogen includes at least one of fluorine, chlorine and bromine.

[0149] Halogenated cyclohexane is a six-membered cyclic hydrocarbon, and its structural stability is worse than that of halogenated benzene, and hydrocarbon chain scission is prone to occur at high temperatures. Halogenated cyclohexane can be, for example, chlorocyclohexane, hexachlorocyclohexane, hexabromocyclohexane, trichlorocyclohexane. Halogenated benzene can be, for example, tribromobenzene, hexachlorobenzene, hexabromobenzene, etc. Halogenated benzoic acid can be, for example, chlorobenzoic acid, bromobenzoic acid, 2-bromobenzoic acid, 4-bromobenzoic acid, 3-chlorobenzoic acid, etc. Halogenated aniline can be, for example, p-chloroaniline, 4-bromoaniline, 2-chloroaniline, etc.

[0150] When the halogen-containing six-membered ring organic compound is halogenated cyclohexane, before performing step S300, the method further includes step S201:

[0151] A cleavage inhibitor is added to the mixture, wherein the cleavage inhibitor includes an amide compound and a cyanate. The amide compound includes at least one of carbon amide, formamide, acetamide, dimethylformamide and lactam; and the cyanate includes at least one of potassium cyanate, sodium cyanate and ammonium cyanate.

[0152] It should be noted that carbonamide will decompose and deaminate into isocyanic acid when heated to (150°C to 160°C). Potassium cyanate can decompose into potassium cyanamide and carbon dioxide at high temperature (700°C to 900°C) and insulated from air. Similarly, sodium cyanate decomposes into sodium cyanamide and carbon dioxide at about 550°C. It can be understood that the decomposed carbon dioxide gas and inorganic salts are harmless to the environment, and the cracking inhibitor can undergo a decomposition reaction at high temperature and insulated from air, absorbing part of the reaction energy, thereby inhibiting the self-cracking of the halogenated cyclohexane or its derivatives.

[0153] In a specific embodiment, the molar ratio of the NM alloy to the amide compound is 1:(0.1-10), for example, it can be 1:0.1, 1:0.5, 1:1, 1:5 or 1:10, etc., which is not limited here. The molar ratio of the silicon alloy to the cyanate is 1:(0.1-10), for example, it can be 1:0.1, 1:0.5, 1:1, 1:5 or 1:10, etc., which is not limited here.

[0154] S300, subjecting the mixture to a replacement reaction under a protective atmosphere to obtain a reaction product, wherein the reaction product includes an oxide of M and a halide of M;

[0155] In a specific embodiment, in order to fully react the mixture, the temperature of the replacement reaction is 200°C to 1000°C, for example, 200°C, 300°C, 400°C, 600°C, 800°C or 950°C.

[0156] The insulation time is 1 h to 24 h, for example, it can be 1 h, 3 h, 6 h, 9 h, 12 h, 15 h, 18 h or 24 h, which is not limited here.

[0157] Among them, when the temperature is 200-750°C, the generated carbon layer is an amorphous carbon layer; when it is greater than 750°C, the generated carbon layer is wrinkled graphene.

[0158] The heating rate of the replacement reaction is 1°C / min to 20°C / min, for example, 1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min, thereby effectively improving the reaction efficiency.

[0159] It can be understood that within the above-mentioned suitable heat treatment temperature, time and heating rate range, it is helpful to improve the dealloying efficiency and help the silicon alloy to form a skeleton structure during the dealloying process.

[0160] In order to improve the safety of the reaction, the replacement reaction is carried out under protective atmosphere conditions, wherein the protective atmosphere gas includes at least one of nitrogen, helium, neon, argon and xenon. The flow rate of the protective gas can be controlled at 1 L / min-10 L / min.

[0161] S400, removing the oxide of M and the halide of M to obtain a composite negative electrode material.

[0162] It should be noted that the reaction products include halides of M, oxides of M, carbon and N. Therefore, it is necessary to remove the metal oxides and halides in the reaction products.

[0163] As an optional technical solution of the present application, the removal method includes pickling, and the reaction product is pickled to remove metal oxides and halides in the reaction product.

[0164] Optionally, the acid solution used for pickling includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

[0165] The mass concentration of the acid solution is 1 mol / L to 5 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L. Of course, the mass concentration of the acid solution can also be adjusted according to actual needs, which is not limited here.

[0166] The pickling time is 1 hour to 10 hours, for example, 1 hour, 3 hours, 5 hours, 7 hours or 10 hours. In this embodiment, the pickling product can still be recycled.

[0167] In this scheme, the negative electrode material is prepared by a one-step composite method. The NM alloy directly reacts with the six-membered ring organic matter at high temperature to remove the metal M component in the NM alloy, and at the same time, a carbon layer is deposited in situ on the surface of the N material. The overall reaction is mild and has no by-products. The structure of the N material is complete and stable, and the carbon layer is deposited evenly. The raw materials involved in the reaction are commonly used alloys, organic matter and metal salts, which can reduce costs.

[0168] In this scheme, the graphene layer and the amorphous carbon layer are formed by in-situ growth. A composite negative electrode material is prepared by one-step dealloying with a halogen-containing six-membered ring organic matter as a carbon source and an NM alloy. The method utilizes the strong reducing property of the metal vapor generated in the NM alloy at high temperature, and removes the metal M component in the NM alloy after reacting with the six-membered ring organic matter. The six-membered ring itself grows in situ and self-assembles in an orderly manner to form a wrinkled graphene layer or an amorphous carbon layer. After pickling, the wrinkled graphene or amorphous carbon layer is obtained to wrap the N material. The composite negative electrode material is prepared by a one-step composite method, which can effectively improve the preparation efficiency. The preparation method is simple and easy, green and environmentally friendly, the preparation process is highly controllable, the cost is low and can be mass-produced. The prepared composite negative electrode material has the advantages of high capacity, high charge and discharge cycle stability, low expansion rate, etc., and can be widely used in lithium batteries. It should be noted that the one-step composite method refers to the simultaneous preparation of silicon material and carbon coating, and its preparation efficiency is higher than that of the two-step composite method.

[0169] The composite negative electrode material prepared by the method of this embodiment includes a core 10 and a coating layer 20 formed on the surface of the core 10; wherein,

[0170] The inner core 10 is a primary particle. The primary particle includes a skeleton. The skeleton includes a main skeleton 11 located inside the primary particle and a plurality of branches 12 extending from the main skeleton 11 to the surface of the primary particle.

[0171] The core 10 of this embodiment is a primary particle, and the primary particle has a macroporous structure. A pore 13 is formed inside the primary particle, and the pore 13 extends to the surface of the primary particle.

[0172] The coating layer 20 is a carbon coating layer.

[0173] For example, Figure 5 Schematic diagram of the synthesis process of silicon-carbon composite negative electrode materials.

[0174] When the coating layer is a metal oxide layer, a method for preparing a composite negative electrode material in one embodiment includes the following steps S100′ to S400′:

[0175] S100′, preparing N1-M1 material;

[0176] In some embodiments, the N1-M1 material is at least one of an intermetallic compound and an alloy;

[0177] Among them, N1 in the N1-M1 material includes at least one of silicon, germanium, antimony, tin, and boron; and M1 in the N1-M1 material includes at least one of magnesium, aluminum, calcium, and zinc.

[0178] Specifically, the preparation method of the N1-M1 alloy is the same as step S100; it will not be described in detail here;

[0179] S200′, forming a metal oxide layer on the surface of the N1-M1 material to obtain a composite;

[0180] In a specific embodiment, the metal element of the metal oxide layer includes at least one of Ti, V, Nb, Ta, W and Zr. The molar ratio of the metal element to the oxygen element in the metal oxide layer is 1:(0.1-3);

[0181] In some embodiments, the metal oxide layer has a thickness of 1 nm to 200 nm.

[0182] Specifically, the molar ratio of the N1-M1 material to the metal oxide of the metal oxide layer is 1:(0.01-5), for example, it can be 1:0.02, 1:0.05, 1:1, 1:2, 1:3, 1:4 or 1:5, which is not limited here.

[0183] Specifically, the method for forming the metal oxide layer on the surface of the N1-M1 material adopts a conventional method in the art, such as a hydrothermal method, a sol-gel method, a precipitation method, a chemical vapor deposition method, a magnetron sputtering method or a solid phase reaction method;

[0184] S300′, subjecting the complex to a replacement reaction under a vacuum environment to obtain a reaction product;

[0185] Specifically, the reaction products include oxides of M1, N1, and metal oxides;

[0186] In some embodiments, the vacuum degree in the vacuum environment is less than 1000 Pa;

[0187] The temperature of the substitution reaction is 500°C to 1100°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C or 1200°C.

[0188] The insulation time of the replacement reaction is 1 h to 48 h, for example, 1 h, 24 h, 36 h or 48 h, which is not limited here.

[0189] The heating rate of the reduction reaction is 1°C / min to 20°C / min, for example, 1°C / min, 3°C / min, 5°C / min, 8°C / min or 20°C / min, which is not limited here.

[0190] S400′, removing the oxide of M1 to obtain a composite negative electrode material;

[0191] Specifically, the method of removing the oxide of M1 includes pickling;

[0192] Furthermore, the acid solution used for pickling includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

[0193] The mass concentration of the acid solution is 1 mol / L to 5 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L or 5 mol / L. Of course, the mass concentration of the acid solution can also be adjusted according to actual needs, which is not limited here.

[0194] The duration of pickling is 1 hour to 10 hours, for example, 1 hour, 3 hours, 5 hours, 7 hours or 10 hours. In this embodiment, the pickling product can still be recycled.

[0195] In this embodiment, a metal oxide layer is coated on the surface of the N1-M1 material, and the N1-M1 material undergoes a replacement reaction with part of the metal oxide layer at high temperature, thereby removing the M1 component in the N1-M1 material and generating an incompletely reacted metal oxide layer on the surface of the N1 material. After pickling, a composite negative electrode material can be obtained. In this solution, the metal oxide layer has the advantages of good rigidity and excellent density, and the current and flexible carbon layer material can effectively inhibit the volume expansion of N1 and cause the destruction of the entire structure, reduce the volume expansion of the material, and avoid contact between the electrolyte and the silicon negative electrode, reduce side reactions, and improve the primary effect of the entire composite material.

[0196] The composite negative electrode material prepared by the preparation method of the composite negative electrode material provided in the embodiment of the present invention can effectively improve the stability of the charge and discharge cycle of the lithium battery, and has multiple advantages such as high capacity, long cycle life, high initial efficiency and low expansion.

[0197] The composite negative electrode material prepared by the method of this embodiment includes a core 10 and a coating layer 20 formed on the surface of the core 10; wherein,

[0198] The inner core 10 is a primary particle. The primary particle includes a skeleton. The skeleton includes a main skeleton 11 located inside the primary particle and a plurality of branches 12 extending from the main skeleton 11 to the surface of the primary particle.

[0199] The core 10 of this embodiment is a primary particle, and the primary particle has a macroporous structure. A pore 13 is formed inside the primary particle, and the pore 13 extends to the surface of the primary particle.

[0200] The coating layer 20 is a metal oxide layer.

[0201] When the coating layer is a metal nitride layer, a method for preparing a composite negative electrode material in one embodiment includes the following steps S100″ to S400″:

[0202] S100″, preparation of N1-M1 materials;

[0203] S200″, forming a metal oxide layer on the surface of the N1-M1 material to obtain a composite;

[0204] Steps S100 ″ and S200 ″ are the same as steps S100 ′ and S200 ′ described above, and are not described again herein.

[0205] S300″, subjecting the composite to heat treatment under a protective atmosphere and then to nitridation treatment to obtain a reaction product;

[0206] Wherein, the reaction products include oxides of M1, N1, and metal oxides;

[0207] The heat treatment temperature in the protective atmosphere is 500-800°C, the holding time is 1h-24h, and the reaction heating rate of the heat treatment is 1-20°C / min;

[0208] The protective atmosphere includes at least one of helium, neon, argon, krypton and xenon;

[0209] Specifically, in the nitriding treatment, the treatment temperature is 400-950° C., and the holding time is 2 h to 24 h; the nitriding atmosphere is at least one of an ammonia atmosphere and a plasma nitrogen atmosphere.

[0210] S400″, removing the oxide of M1 to obtain a composite negative electrode material;

[0211] The method of removing the oxide of M1 is the same as step S400 ′ and will not be described again herein.

[0212] The composite negative electrode material prepared by the method of this embodiment includes a core 10 and a coating layer 20 formed on the surface of the core 10; wherein,

[0213] The inner core 10 is a primary particle. The primary particle includes a skeleton. The skeleton includes a main skeleton 11 located inside the primary particle and a plurality of branches 12 extending from the main skeleton 11 to the surface of the primary particle.

[0214] The core 10 of this embodiment is a primary particle, and the primary particle has a macroporous structure. A pore 13 is formed inside the primary particle, and the pore 13 extends to the surface of the primary particle.

[0215] The coating layer 20 is a metal nitride layer.

[0216] In this embodiment, after coating a metal oxide layer on the surface of the N1-M1 material, heat treatment is performed under a protective atmosphere, on the one hand, to ensure that the N1-M1 material undergoes a replacement reaction with part of the metal oxide layer to remove the metal M1 component in the N1-M1 material; on the other hand, to ensure that the oxide is transformed from amorphous to crystalline at high temperature and normal pressure. Further nitridation treatment is performed to nitride the metal oxide layer on the surface of the inner core into metal nitride, and then pickling is performed to obtain a composite negative electrode material. In this solution, the metal nitride layer not only has good rigidity, but also has excellent conductivity, which can effectively alleviate the volume expansion of silicon while increasing the conductivity of the material, improving the rate capability of the material, reducing the irreversible capacity loss of the material, and bringing high capacity.

[0217] For example, Figure 5 Schematic diagram of the synthesis process of silicon / metal oxide and silicon / metal nitride composite negative electrode materials;

[0218] The composite negative electrode material prepared by the preparation method of the composite negative electrode material provided in the embodiment of the present invention can effectively improve the stability of the charge and discharge cycle of the lithium battery, and has multiple advantages such as high capacity, long cycle life, good rate performance and low expansion.

[0219] The embodiments of the present invention also provide a lithium ion battery negative electrode plate and a lithium ion battery, using the composite negative electrode material provided by the above embodiments of the present invention or the negative electrode material prepared by the method for preparing the composite negative electrode material provided by the above embodiments of the present invention.

[0220] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0221] Example 1

[0222] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0223] (1) Silicon powder with a particle size of 1 μm and magnesium powder were mixed evenly in a molar ratio of 1:2 and placed in an atmosphere furnace. Under the protection of argon inert gas, the mixture was heated to 600°C at a heating rate of 3°C / min and then kept at this temperature for 6 h to allow the mixture to fully react and obtain a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain a 1 μm silicon-magnesium alloy powder.

[0224] (2) 1 mol of silicon-magnesium alloy powder and 1 mol of hexachlorocyclohexane are uniformly mixed, and then 1 mol each of carbonamide, potassium cyanate and sodium cyanate are added to obtain a mixture.

[0225] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 10 Pa. Then, the reactor is heated to 780° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react, thereby obtaining a reaction product;

[0226] (4) The reaction product was treated with mechanical stirring for 2 h in a 1 mol / L hydrochloric acid solution, and then filtered, washed, and dried to obtain a silicon-carbon composite negative electrode material.

[0227] The median particle size of the obtained silicon-carbon composite negative electrode material is about 1 μm, and the specific surface area is 53 m 2 / g, the porosity is 48%, and the mass percentage content of carbon is 12%.

[0228] Figure 6a , Figure 6b This is a scanning electron microscope image of the silicon-carbon composite negative electrode material. Figure 7 Raman image of the silicon-carbon composite negative electrode material provided in this embodiment; Figure 8 The XRD pattern of the silicon-carbon composite negative electrode material provided in this embodiment is as follows: Figure 6a , Figure 6b It can be seen from the scanning electron microscope image in that the silicon-carbon composite negative electrode material of the obtained product includes a core and a coating layer formed on the surface of the core; wherein,

[0229] The inner core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore channel is formed inside the primary particle, and the pore channel extends to the surface of the primary particle.

[0230] The coating layer is 2nm wrinkled graphene. The average diameter of the pores is about 100nm, and the depth of the pores is about 700nm.

[0231] Figure 7 The Raman spectrum further proves that at 2680 cm -1 There is a 2D peak nearby, which is a characteristic peak of graphite, further indicating that the in-situ generated carbon is graphite-like carbon with better conductivity and stability. Figure 8 It can be seen from the XRD spectrum that the three strong peaks at 28.4°, 47.3° and 56.1° correspond to the three strong peaks of silicon (JCPDS No.27-1402), and there is basically no impurity phase.

[0232] Example 2

[0233] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0234] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5 and placed in an atmosphere furnace. The mixture was heated to 650° C. at a heating rate of 5° C. / min under the protection of argon inert gas and then kept at this temperature for 6 h to allow the mixture to fully react and obtain a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain a 0.5 μm silicon-magnesium alloy powder.

[0235] (2) 1 mol of silicon-magnesium alloy powder and 1 mol of hexachlorobenzene are uniformly mixed to obtain a mixture.

[0236] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 100 Pa. Then, the reactor is heated to 650° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react and obtain a reaction product;

[0237] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon composite negative electrode material.

[0238] The median particle size of the silicon-carbon composite negative electrode material is about 0.6 μm, and the specific surface area is 79 m 2 / g, the porosity is 56%, and the mass percentage content of carbon is 20%.

[0239] The silicon-carbon composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein,

[0240] The core is a primary particle, the primary particle includes a silicon skeleton, the skeleton includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, a pore is formed inside the primary particle, and the pore extends to the surface of the primary particle.

[0241] The coating layer is a 10nm amorphous carbon layer, the average diameter of the pores is about 130nm, and the depth of the pores is about 800nm.

[0242] Example 3

[0243] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0244] (1) 12 μm silicon powder and magnesium powder were mixed evenly in a molar ratio of 1:2 and placed in an atmosphere furnace, and heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept at this temperature for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 10 μm silicon-magnesium alloy powder;

[0245] (2) 1 mol of silicon-magnesium alloy powder and 1 mol of hexachlorobenzene are uniformly mixed to obtain a mixture.

[0246] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 100 Pa. Then, the reactor is heated to 800° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow it to fully react and obtain a reaction product;

[0247] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon composite negative electrode material.

[0248] The median particle size of the obtained silicon-carbon composite negative electrode material is about 10 μm, and the specific surface area is 43 m 2 / g, porosity is 61%, and carbon content by mass is 15%;

[0249] The silicon-carbon composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein,

[0250] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore channel is formed inside the primary particle, and the pore channel extends to the surface of the primary particle.

[0251] The coating layer is a 5nm wrinkled graphene layer, the average diameter of the three-dimensional pores is about 110nm, and the pore depth of the three-dimensional pores is about 670nm.

[0252] Example 4

[0253] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0254] (1) 1 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:1.2, and then placed in an atmosphere furnace, and heated to 600°C at a heating rate of 5°C / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 1 μm silicon-magnesium alloy powder;

[0255] (2) 1 mol of silicon-magnesium alloy powder and 0.5 mol of hexachlorobenzene are uniformly mixed to obtain a mixture.

[0256] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 10 Pa. Then, the reactor is heated to 800° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react, thereby obtaining a reaction product;

[0257] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a composite negative electrode material.

[0258] The median particle size of the obtained silicon-carbon composite negative electrode material is about 1 μm, and the specific surface area is 38 m 2 / g, the porosity is 47%, and the mass percentage content of carbon is 5%.

[0259] The silicon-carbon composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein,

[0260] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and multiple branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, with pores formed inside the primary particle, which extend to the surface of the primary particle; the coating layer is a 4nm wrinkled graphene layer; the average diameter of the pores is about 65nm, and the depth of the three-dimensional pores is about 680nm.

[0261] Example 5

[0262] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0263] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5, and then placed in an atmosphere furnace, heated to 800° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 0.5 μm silicon-magnesium alloy powder;

[0264] (2) 1 mol of silicon-magnesium alloy powder and 4 mol of hexachlorobenzene are uniformly mixed to obtain a mixture.

[0265] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 100 Pa. Then, the reactor is heated to 750° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react and obtain a reaction product;

[0266] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a composite negative electrode material.

[0267] The median particle size of the obtained silicon-carbon composite negative electrode material is about 0.5 μm, and the specific surface area is 80 m 2 / g, the porosity is 53%, and the mass percentage content of carbon is 22%.

[0268] The silicon-carbon composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein,

[0269] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a 6nm wrinkled graphene layer. The average diameter of the pore is about 130nm, and the depth of the pore is about 940nm.

[0270] Example 6

[0271] A method for preparing a germanium-carbon composite negative electrode material comprises the following steps:

[0272] (1) 1.5 μm germanium powder and magnesium powder were mixed evenly in a molar ratio of 1:2.5, and then placed in an atmosphere furnace, heated to 480° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain a germanium-magnesium alloy; the germanium-magnesium alloy was ball-milled to obtain a 0.5 μm germanium-magnesium alloy powder;

[0273] (2) 1 mol of germanium-magnesium alloy powder and 3 mol of hexachlorobenzene are uniformly mixed to obtain a mixture.

[0274] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 100 Pa. Then, the reactor is heated to 600° C. at a heating rate of 3° C. / min in an argon atmosphere and then kept at this temperature for 8 h to allow it to fully react and obtain a reaction product;

[0275] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a composite negative electrode material.

[0276] The median particle size of the obtained germanium-carbon composite negative electrode material is about 0.6 μm, and the specific surface area is 75 m 2 / g, the porosity is 63%, and the mass percentage content of carbon is 18%.

[0277] The germanium-carbon composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein,

[0278] The core is a primary particle, which includes a germanium skeleton, which includes a main skeleton located inside the primary particle and multiple branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore channel is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a 12nm amorphous carbon layer. The average pore diameter of the three-dimensional pore channel is about 120nm, and the pore depth of the three-dimensional pore channel is about 35nm.

[0279] Example 7

[0280] A method for preparing a silicon-carbon composite negative electrode material comprises the following steps:

[0281] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5 and placed in an atmosphere furnace, heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 0.5 μm silicon-magnesium alloy powder;

[0282] (2) 1 mol of silicon-magnesium alloy powder, 2.6 mol of chlorocyclohexane and 0.5 mol of carbonamide were uniformly mixed to obtain a mixture.

[0283] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 100 Pa. Then, the reactor is heated to 750° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react and obtain a reaction product;

[0284] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon composite negative electrode material.

[0285] The median particle size of the obtained silicon-carbon composite negative electrode material is about 0.5 μm, and the specific surface area is 64 m 2 / g, the porosity is 53%, and the mass percentage content of carbon is 19%.

[0286] The silicon-carbon composite negative electrode material comprises a core and a coating layer formed on the surface of the core; wherein,

[0287] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a 3.2nm wrinkled graphene layer, the average diameter of the pore is about 110nm, and the depth of the pore is about 780nm.

[0288] Example 8

[0289] A method for preparing a silicon composite negative electrode material comprises the following steps:

[0290] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5 and placed in an atmosphere furnace, heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 0.5 μm silicon-magnesium alloy powder;

[0291] (2) 1 mol of silicon-magnesium alloy powder and 0.7 g of cellulose are dissolved in 500 ml of anhydrous ethanol and dispersed evenly to obtain a mixed solution.

[0292] (3) 3 g of tetrabutyl titanate was added dropwise to the mixed solution, heated to 80° C., rapidly stirred for 3 hours, and then filtered. After vacuum drying at 60° C. for 24 hours, a titanium oxide precursor-encapsulated silicon-magnesium alloy composite was obtained;

[0293] (4) placing the above-mentioned composite into a sealed stainless steel reactor, evacuating the pressure to 100 Pa, and then heating the reactor to 750° C. at a heating rate of 3° C. / min in an argon atmosphere and then keeping the temperature for 8 h to allow the reaction to fully react, thereby obtaining a reaction product;

[0294] (4) The reaction product was placed in 4 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon / titanium oxide composite negative electrode material.

[0295] The median particle size of the obtained composite negative electrode material is about 0.6 μm, and the specific surface area is 44 m 2 / g, the porosity is 43%, and the mass percentage content of titanium oxide is 12%.

[0296] The composite negative electrode material includes a core and a coating layer formed on the surface of the core; wherein,

[0297] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and multiple branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a titanium oxide layer. The average diameter of the pore is about 20nm, and the depth of the pore is about 150nm.

[0298] Example 9

[0299] A method for preparing a silicon composite negative electrode material comprises the following steps:

[0300] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5 and placed in an atmosphere furnace, heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 0.5 μm silicon-magnesium alloy powder;

[0301] (2) 1 mol of silicon-magnesium alloy powder and 0.7 g of cellulose are dissolved in 500 ml of anhydrous ethanol and dispersed evenly to obtain a mixed solution.

[0302] (3) 4 g of tetrabutyl titanate was added dropwise to the mixed solution, heated to 80° C., rapidly stirred for 3 hours, and then filtered. After vacuum drying at 60° C. for 24 hours, a titanium oxide precursor-encapsulated silicon-magnesium alloy composite was obtained;

[0303] (4) placing the above-mentioned composite into a tubular atmosphere furnace, heating it to 650°C at a heating rate of 3°C / min in an argon atmosphere, and then keeping it at this temperature for 5 hours to allow it to fully react, then replacing the argon with ammonia, raising the temperature to 800°C, and keeping it at this temperature for 8 hours to obtain a reaction product;

[0304] (4) The reaction product was placed in 4 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon / titanium nitride composite negative electrode material.

[0305] The median particle size of the obtained composite negative electrode material is about 0.7 μm, and the specific surface area is 40 m 2 / g, the porosity is 48%, and the mass percentage content of titanium nitride is 32%.

[0306] The composite negative electrode material includes a core and a coating layer formed on the surface of the core; wherein,

[0307] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a titanium nitride layer. The average diameter of the pore is about 50nm, and the depth of the pore is about 400nm.

[0308] Example 10

[0309] A method for preparing a silicon composite negative electrode material comprises the following steps:

[0310] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5 and placed in an atmosphere furnace, heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain silicon-magnesium alloy; the silicon-magnesium alloy was ball-milled to obtain 0.5 μm silicon-magnesium alloy powder;

[0311] (2) Vanadium pentoxide-coated silicon-magnesium alloy was prepared by a sol-gel process. First, 500 ml of an alcohol solution of triisopropoxy vanadium oxide with a concentration of 0.15 M / L was prepared, and 30 ml of acetylacetone was added to obtain a mixed solution. 0.5 mol of silicon-magnesium alloy powder was added to the mixed solution and stirred for 36 hours, and then dispersed evenly to obtain a sol.

[0312] (3) the sol is filtered and vacuum dried at 60° C. for 24 hours to obtain a vanadium pentoxide precursor-encapsulated silicon-magnesium alloy composite;

[0313] (4) placing the above-mentioned composite into a tubular atmosphere furnace, heating it to 600°C at a heating rate of 3°C / min in an argon atmosphere, and then keeping it at this temperature for 3 hours to allow it to fully react, then replacing the argon with ammonia, raising the temperature to 750°C, and keeping it at this temperature for 8 hours to obtain a reaction product;

[0314] (5) The reaction product was placed in 4 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon / vanadium nitride composite negative electrode material.

[0315] The median particle size of the obtained composite negative electrode material is about 0.6 μm, and the specific surface area is 51 m 2 / g, the porosity is 40%, and the mass percentage content of titanium nitride is 25%.

[0316] The composite negative electrode material includes a core and a coating layer formed on the surface of the core; wherein,

[0317] The core is a primary particle, which includes a silicon skeleton, which includes a main skeleton located inside the primary particle and multiple branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a 60nm vanadium nitride layer. The average diameter of the pore is about 125nm, and the depth of the pore is about 350nm.

[0318] Embodiment 11

[0319] A method for preparing a composite negative electrode material comprises the following steps:

[0320] (1) 1.5 μm germanium powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5, and then placed in an atmosphere furnace, heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain a germanium-magnesium alloy; the germanium-magnesium alloy was ball-milled to obtain a 0.5 μm germanium-magnesium alloy powder;

[0321] (2) 1 mol of germanium-magnesium alloy powder and 0.7 g of cellulose are dissolved in 500 ml of anhydrous ethanol and dispersed evenly to obtain a mixed solution.

[0322] (3) 3 g of tetrabutyl titanate was added dropwise to the mixed solution, heated to 80° C., rapidly stirred for 3 hours, filtered, and vacuum dried at 60° C. for 24 hours to obtain a germanium-magnesium alloy composite wrapped with a titanium oxide precursor;

[0323] (4) placing the above-mentioned composite into a sealed stainless steel reactor, evacuating the pressure to 100 Pa, and then heating the reactor to 750° C. at a heating rate of 3° C. / min in an argon atmosphere and then keeping the temperature for 8 h to allow the reaction to fully react, thereby obtaining a reaction product;

[0324] (4) The reaction product was placed in 4 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous germanium / titanium oxide composite negative electrode material.

[0325] The median particle size of the obtained composite negative electrode material is about 0.55 μm, and the specific surface area is 41 m 2 / g, the porosity is 45%, and the mass percentage content of titanium oxide is 13%.

[0326] The composite negative electrode material includes a core and a coating layer formed on the surface of the core; wherein,

[0327] The core is a primary particle, which includes a germanium skeleton, which includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a titanium oxide layer. The average diameter of the pore is about 600nm, and the depth of the pore is about 180nm.

[0328] Example 12

[0329] A method for preparing a composite negative electrode material comprises the following steps:

[0330] (1) 1.5 μm germanium powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5, and then placed in an atmosphere furnace, heated to 600° C. at a heating rate of 5° C. / min under the protection of argon inert gas, and then kept warm for 6 hours to fully react to obtain a germanium-magnesium alloy; the germanium-magnesium alloy was ball-milled to obtain a 1.0 μm germanium-magnesium alloy powder;

[0331] (2) Vanadium pentoxide-coated germanium-magnesium alloy was prepared by a sol-gel process. First, 500 ml of an alcohol solution of triisopropoxy vanadium oxide with a concentration of 0.1 M / L was prepared, and 30 ml of acetylacetone was added to obtain a mixed solution. 0.5 mol of germanium-magnesium alloy powder was added to the mixed solution and stirred for 36 hours, and then dispersed evenly to obtain a sol.

[0332] (3) the sol is filtered and vacuum dried at 60° C. for 24 hours to obtain a vanadium pentoxide precursor-encapsulated germanium-magnesium alloy composite;

[0333] (4) placing the above-mentioned composite into a tubular atmosphere furnace, heating it to 600°C at a heating rate of 3°C / min in an argon atmosphere, and then keeping it at this temperature for 3 hours to allow it to fully react, then replacing the argon with ammonia, raising the temperature to 750°C, and keeping it at this temperature for 8 hours to obtain a reaction product;

[0334] (5) The reaction product was placed in 4 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous germanium / vanadium nitride composite negative electrode material.

[0335] The median particle size of the obtained composite negative electrode material is about 1.2 μm, and the specific surface area is 52 m 2 / g, the porosity is 43%, and the mass percentage content of titanium nitride is 24%.

[0336] The composite negative electrode material includes a core and a coating layer formed on the surface of the core; wherein,

[0337] The core is a primary particle, which includes a germanium skeleton, which includes a main skeleton located inside the primary particle and multiple branches extending from the main skeleton to the surface of the primary particle. The primary particle is a macroporous structure, and a pore is formed inside the primary particle, which extends to the surface of the primary particle; the coating layer is a 50nm vanadium nitride layer. The average diameter of the pore is about 150nm, and the depth of the pore is about 900nm.

[0338] Example 13

[0339] A method for preparing a composite negative electrode material comprises the following steps:

[0340] (1) 1.5 μm silicon powder and magnesium powder were mixed evenly at a molar ratio of 1:2.5 and placed in an atmosphere furnace. The mixture was heated to 650° C. at a heating rate of 5° C. / min under the protection of argon inert gas and then kept at this temperature for 6 h to allow the mixture to fully react and obtain a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain a 0.5 μm silicon-magnesium alloy powder.

[0341] (2) 1 mol of silicon-magnesium alloy powder and 0.1 mol of hexachlorobenzene are uniformly mixed to obtain a mixture.

[0342] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 100 Pa. Then, the reactor is heated to 750° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react and obtain a reaction product;

[0343] (4) The reaction product was placed in 2 L of 1 mol / L hydrochloric acid solution and subjected to mechanical stirring and pickling treatment for 3 h, and then filtered, washed, and dried to obtain a porous silicon composite negative electrode material.

[0344] The median particle size of the obtained silicon-carbon composite negative electrode material is about 0.6 μm, and the specific surface area is 79 m 2 / g, the porosity is 56%, the mass percentage of carbon is 20%, the average diameter of the pores is about 130nm, and the depth of the pores is about 800nm.

[0345] Embodiment 14

[0346] (1) Silicon powder with a particle size of 1 μm and magnesium powder were mixed evenly in a molar ratio of 1:2 and placed in an atmosphere furnace. Under the protection of argon inert gas, the mixture was heated to 600°C at a heating rate of 3°C / min and then kept at this temperature for 6 h to allow the mixture to fully react and obtain a silicon-magnesium alloy. The silicon-magnesium alloy was ball-milled to obtain a 1 μm silicon-magnesium alloy powder.

[0347] (2) 1 mol of silicon-magnesium alloy powder and 2.6 mol of hexachlorocyclohexane are uniformly mixed to obtain a mixture.

[0348] (3) After the obtained mixture is mixed evenly, it is placed in a sealed stainless steel reactor and evacuated to 10 Pa. Then, the reactor is heated to 750° C. at a heating rate of 3° C. / min in an argon atmosphere and kept at this temperature for 8 h to allow the reaction to fully react and obtain a reaction product;

[0349] (4) The reaction product was treated with mechanical stirring for 2 h in a 1 mol / L hydrochloric acid solution, and then filtered, washed, and dried to obtain a silicon-carbon composite negative electrode material.

[0350] The median particle size of the obtained silicon-carbon composite negative electrode material is about 1 μm, and the specific surface area is 77 m 2 / g, the porosity is 56%, the mass percentage content of carbon is 19%, the median particle size of the primary particles is about 0.5μm, the average pore diameter of the three-dimensional channel is about 100nm, the pore depth of the three-dimensional channel is about 730nm, the graphene layer cannot be formed, and the carbon layer thickness is 25nm.

[0351] Comparative Example 1

[0352] The silicon-carbon composite negative electrode material SiO / C is used. The median particle size of the silicon-carbon composite negative electrode material is 1.5μm. The core of the composite material is a porous silicon structure with nano-silicon particles accumulated, and the outer shell is wrapped with a carbon layer. Among them, the mass percentage of carbon is 22%, and the specific surface area is 38m 2 / g, the thickness of the carbon layer is 50nm, and the porosity of the silicon-carbon composite negative electrode material is 67%. That is, it is a SiOx / C negative electrode material, where x=1.0.

[0353] In summary, the negative electrode materials prepared in Examples 1 to 14 and Comparative Example 1 have sample numbers corresponding to S1 to S14 and R1; the performance parameters of the negative electrode materials are shown in Table 1:

[0354] Table 1

[0355]

[0356] Performance Test:

[0357] The negative electrode material was mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6) and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare a slurry, uniformly coated on a copper foil and dried to make a negative electrode sheet, which was assembled into a button cell in an argon atmosphere glove box. The separator used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.

[0358] The above 15 groups of batteries were tested for discharge specific capacity on a Blue Power CT2001A battery testing system. The ratio of the amount of electricity discharged in one hour to the battery capacity is the discharge specific capacity.

[0359] The 15 groups of batteries mentioned above were subjected to the first coulombic efficiency test on the Blue Power CT2001A battery testing system, with the charge and discharge current being 0.05C, and the first coulombic efficiency was measured.

[0360] The 15 groups of batteries mentioned above were cycled for 100 cycles on a Blue Power CT2001A battery testing system with a charge and discharge current of 0.2C. After 100 cycles, the battery capacity and capacity retention rate after the cycle were calculated.

[0361] Among them, the capacity retention rate after 100 cycles at 0.2C = 100th cycle discharge capacity / first cycle discharge capacity*100%. The results are shown in Table 2.

[0362] Table 2 Parameter performance comparison of each battery

[0363]

[0364] The composite negative electrode material of the present application has the advantages of low expansion and good cycle stability.

[0365] It can be seen from Tables 1 to 2 above that the main difference between Example 13 and Example 2 is that the mixing ratio of silicon-magnesium alloy and hexachlorobenzene is relatively low, which leads to a significant decrease in the thickness of the graphene layer on the surface of the silicon material, which is not conducive to increasing the conductivity of the negative electrode material and has a weak performance in inhibiting the volume expansion of the material, resulting in poor long cycle performance.

[0366] The main difference between Example 14 and Example 1 is that no cleavage inhibitor (carbonamide, potassium cyanate and sodium cyanate) is added, and chlorocyclohexane is decomposed in large quantities during the reaction, making it difficult to deposit on the surface of the silicon material to form a graphene layer, resulting in a decrease in the battery's charge and discharge specific capacity, first coulomb efficiency, and capacity retention rate after the cycle. Comparative Example 1 is a carbon-coated porous silicon negative electrode material. The capacity and capacity retention rate of the battery made of this material are both reduced after 100 cycles of 0.2C cycling, and the electrode film expansion rate of Comparative Example 1 is also higher than that of Example 1.

[0367] In summary, the preparation method of the silicon-carbon composite negative electrode material provided in the present application is simple and easy to operate, and the preparation process is safe and efficient; the manufacturing cost is effectively reduced and is suitable for mass production; the obtained product is used as a battery electrode and has good charge and discharge cycle performance.

[0368] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A composite negative electrode material, characterized in that: The composite negative electrode material comprises a core and a coating layer located on the surface of the core; wherein, The inner core is a primary particle, the primary particle includes a skeleton, the skeleton includes a main skeleton located inside the primary particle and a plurality of branches extending from the main skeleton to the surface of the primary particle, the main skeleton is a three-dimensional network structure, a single branch is a separate grain, and the size of the grain is 30nm-100nm; The primary particle has a macroporous structure, and channels are formed inside the primary particle, and the channels extend to the surface of the primary particle; the porosity of the primary particle is 30% to 70%; the diameter of the channel is 10nm-150nm; the depth of the channel is 50nm-1500nm.

2. The composite negative electrode material according to claim 1, characterized in that: The branches are selected from at least one of rod-shaped nanoparticles, nanosheets, nanowires and nanotubes.

3. The composite negative electrode material according to claim 1, characterized in that: The porosity of the primary particles is not less than 30%.

4. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The coating layer includes at least one of a carbon layer, a metal oxide layer and a metal nitride layer; and / or The coating layer comprises a carbon layer, and the mass percentage content of carbon is 2% to 50% based on the mass percentage content of the composite negative electrode material being 100%; and / or The coating layer comprises a metal oxide layer, and the mass percentage content of the metal oxide is 2% to 60% based on the mass percentage content of the composite negative electrode material being 100%; and / or The coating layer comprises a metal nitride layer. Taking the mass percentage of the composite negative electrode material as 100%, the mass percentage of the metal nitride is 2% to 70%.

5. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The composite negative electrode material includes at least one of the following a to e: a. The coating layer comprises at least one of a graphene layer and an amorphous carbon layer; b. The coating layer comprises a graphene layer, wherein the graphene layer has a wrinkled structure; and / or The maximum peak-to-valley height difference of the roughness of the corrugated structure is greater than 10 nm and less than 1 μm, and the distance between two adjacent wave crests or two adjacent wave valleys of the corrugated structure is greater than 10 nm and less than 1 μm; and / or According to the classification of the curvature of the fold surface of the fold structure, the fold structure is selected from at least one of arc folds, sharp-edged folds and fan-shaped folds; and / or According to the axial occurrence and the two-wing occurrence of the fold structure, the fold structure is selected from at least one of upright folds, oblique folds, inverted folds and horizontal folds; c. The coating layer includes an amorphous carbon layer, and the thickness of the amorphous carbon layer is 5nm to 150nm; d. The coating layer comprises a metal oxide layer, wherein the metal element in the metal oxide layer comprises at least one of Ti, V, Nb, Ta, W and Zr; and / or, the molar ratio of the metal element to the oxygen element in the metal oxide layer is 1:(0.1-3); and / or, the thickness of the metal oxide layer is 1nm-200nm; e. The coating layer includes a metal nitride layer, the metal element in the metal nitride layer includes at least one of Ti, V, Nb, Ta, W and Zr, and / or the thickness of the metal nitride layer is 1nm to 250nm.

6. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The composite negative electrode material includes at least one of the following a to h: a. The primary particles are selected from at least one of silicon, germanium, antimony, tin and boron; b. The median particle size of the primary particles is 0.2 μm to 15 μm; c. The specific surface area of ​​the primary particles is 5m 2 / g~100m 2 / g; d. The tap density of the primary particles is 0.2 g / cm 3 ~0.8g / cm 3 ; e. The powder compaction density of the primary particles is 1.2 g / cm 3 ~1.8g / cm 3 ; f. The median particle size of the composite negative electrode material is 0.1 μm to 15 μm; g. The specific surface area of ​​the composite negative electrode material is 1m 2 / g~150m 2 / g; h. The porosity of the composite negative electrode material is 30% to 70%.

7. A method for preparing a composite negative electrode material, characterized in that: The following steps are involved: Placing a mixture containing an NM alloy and a halogen-containing six-membered ring organic compound in a protective atmosphere for a replacement reaction to obtain a reaction product, wherein the reaction product includes an oxide of M and a halide of M; and removing the oxide of M and the halide of M to obtain a composite negative electrode material; Wherein, N in the NM alloy includes at least one of silicon, germanium, antimony, tin and boron, and M in the NM alloy includes at least one of magnesium, aluminum, calcium and zinc.

8. The method for preparing a composite negative electrode material according to claim 7, characterized in that: The preparation method includes at least one of the following features a to f: a. The molar ratio of the NM alloy to the halogen-containing six-membered ring organic compound is 1:(0.2 to 6); b. The halogen-containing six-membered ring organic compound includes at least one of halogenated cyclohexanes and their derivatives, halogenated benzenes, halogenated benzoic acids and halogenated anilines, and the halogen includes at least one of fluorine, chlorine and bromine; c. When the halogen-containing six-membered ring organic compound uses cyclohexane halide, the mixture further comprises a cleavage inhibitor, wherein the cleavage inhibitor comprises an amide compound and a cyanate; and / or The molar ratio of the silicon alloy to the amide compound is 1:(0.1-10); the molar ratio of the silicon alloy to the cyanate is 1:(0.1-10); and / or The amide compound includes at least one of carbonamide, formamide, acetamide, dimethylformamide and lactam; and / or The cyanate includes at least one of potassium cyanate, sodium cyanate and ammonium cyanate; d. The reaction temperature of the replacement reaction is 200 ℃ ~ 1000 ℃, and the reaction time is 1h ~ 24h; e. The protective atmosphere comprises at least one of helium, neon, argon, krypton and xenon; f. The method for removing the oxide of M and the halide of M comprises pickling, wherein the mass concentration of the acid solution used in the pickling is 1 mol / L to 5 mol / L; and / or The acid solution used for pickling includes at least one of hydrochloric acid, nitric acid and sulfuric acid.

9. A method for preparing a composite negative electrode material, characterized in that: The following steps are involved: Performing a replacement reaction on the composite under a vacuum environment to obtain a reaction product, wherein the reaction product includes an oxide of M1, and the composite includes an N1-M1 material having a metal oxide layer formed on the surface; and Removing the oxide of M1 to obtain a composite negative electrode material; Wherein, N1 in the N1-M1 material includes at least one of silicon, germanium, antimony, tin and boron; and M1 in the N1-M1 material includes at least one of magnesium, aluminum, calcium and zinc.

10. The preparation method according to claim 9, characterized in that: The preparation method includes at least one of the following features a to d: a. The vacuum degree under the vacuum environment is less than 1000Pa; b. The temperature of the replacement reaction is 500°C-1100°C, and the insulation time is 1h~48h; c. The method for removing the oxide of M1 is pickling; d. The N1-M1 material is at least one of an intermetallic compound and an alloy.

11. A method for preparing a composite negative electrode material, characterized in that: The following steps are involved: The composite is subjected to heat treatment under a protective atmosphere and then subjected to nitridation treatment to obtain a reaction product, wherein the reaction product comprises an oxide of M1, and the composite comprises an N1-M1 material having a metal oxide layer formed on the surface; and Removing the oxide of M1 to obtain a composite negative electrode material; Wherein, N1 in the N1-M1 material includes at least one of silicon, germanium, antimony, tin and boron; and M1 in the N1-M1 material includes at least one of magnesium, aluminum, calcium and zinc.

12. The preparation method according to claim 11, characterized in that: The preparation method comprises at least one of the following features a to e: a. The method of forming the N1-M1 material having a metal oxide layer on the surface includes at least one of a hydrothermal method, a sol-gel method, a precipitation method, a chemical vapor deposition method, a magnetron sputtering method and a solid phase reaction method; b. The metal element in the metal oxide layer includes at least one of Ti, V, Nb, Ta, W and Zr; c. The heat treatment temperature is 500°C-800°C, and the holding time is 1h to 24h; and / or, the protective atmosphere comprises at least one of helium, neon, argon, krypton and xenon; d. The nitriding treatment is carried out at 400°C-950°C for 2h to 24h; and / or, the atmosphere of the nitriding treatment is at least one of an ammonia atmosphere and a nitrogen atmosphere; e. The method for removing the oxide of M1 is pickling.

13. A lithium ion battery, characterized in that: The invention comprises the composite negative electrode material according to any one of claims 1 to 6 or a negative electrode material prepared according to the method for preparing the composite negative electrode material according to any one of claims 7 to 12.

Citation Information

Patent Citations

  • Honeycomb silicon and carbon composite material and preparation method and application thereof

    CN108023076A